THE TERMINOLOGICAL STRUCTURE IN AL FALAH APPROACH IN DEFINITION AND TERMINOLOGY BY AHMED NUZHAT AL- RAHAWI AL- QUSTANTINI (DIED 1192 AH) - Athraa Dawood Sulayman; Prof. Dr. Mustafa Kamel Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This research aims to describe the formal nature of the terms contained in the lexicon tagged with: The Terminological Structure in Al Falah Approach in Definition and Terminology by Ahmed Nuzhat Al- Rahawi Al- Qustantini (died 1192 AH) which is one of the specialized dictionaries of various sciences or fields. The research plan consisted of an introduction, a preface, two chapters, and a conclusion.